(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
Soil acidity in the humid forest zones of Cameroon is one of the major constraints to agricultural productivity. This study was carried out to assess the rhizobial communities of two acidic soils; with aluminum toxicity (Nkoemvone) and manganese toxicity (Nkolbisson) for their potential to improve soil fertility in Cameroon. These two soils were used to inoculate to the host plants cowpea and siratro. At harvest, 120 rhizobacterial isolates were extracted from the nodules of these two hosts and subjected to morphological characterization. Twenty isolates per site were selected and analyzed for their 16S rDNA genetic profile following restrictions with endonucleases of PCR products and electrophoresis. The restriction patterns of the 16S rDNA of the 40 isolates showed 12 different profiles. Eight occurred in both types of soils, where as 4 were specific to the manganese-toxic-acidic soil. While the Al toxicity reduced the nodulation and growth of both plants, the Mn toxicity mostly affect the cowpea. This study ascertained the distribution of rhizobia based on soil characteristics. Further molecular analyses would allow the identification of the isolates recovered as well as their phylogenetical relationships. Int. J. Agril. Res. Innov. & Tech. 6 (2): 12-23, December, 2016